2007
DOI: 10.1089/aid.2007.0036
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of HIV Type 1 Subtype CenvGene Sequences from India

Abstract: Considering the severity of the HIV-1 subtype C epidemic, data on the epidemiology and distribution of HIV subtypes in India are relatively sparse. Keeping this in view, 28 env gene sequences from patients were sequenced and analyzed. The samples were collected over a period of 10 years from 1995 to 2004. Assessment of the interisolate genetic distances of the study isolates, which were all subtype C, showed interisolate distances varying from 2 to 19% (mean: 14%) with the maximum diversity observed in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
3
13
1
Order By: Relevance
“…The subtype C strains clustered together along with the Indian reference strain (95IN216068). Previous studies performed in different parts of the country also corroborate the predominance of HIV-1 subtype C strains in India [35, 36]. Interestingly, along with subtype C, one stnain each of subtype B and subtype A1 were also found in our patient population.…”
Section: Discussionsupporting
confidence: 89%
“…The subtype C strains clustered together along with the Indian reference strain (95IN216068). Previous studies performed in different parts of the country also corroborate the predominance of HIV-1 subtype C strains in India [35, 36]. Interestingly, along with subtype C, one stnain each of subtype B and subtype A1 were also found in our patient population.…”
Section: Discussionsupporting
confidence: 89%
“…Suggesting thereby, much of the current Indian epidemic is descended from a single introduction into the country [21]. In an assessment of the Phylogenetic relationships among subtype C sequences from eleven different countries including India, an overall star-like phylogeny was observed [10]. Unlike sequences from South Africa and Botswana, which are scattered in numerous lineages, almost all sequences from India formed a monophyletic lineage, which is lying close to the sequences.…”
Section: The Indian Scenariomentioning
confidence: 97%
“…[54][55][56] A breakdown of HIV-1 in Yunnan includes CRF07_BC (18.9%), CRF08_BC (39.1%), and CRF01_AE (22.4%) 57 ; pol sequences in newly diagnosed HIV-infected individuals from Dehong county, Yunnan, showed that subtype C accounted for 43.1%, URF for 18.4%, CRF01_AE for 17.7%, B for 10.7%, CRF08_BC for 8.4%, and CRF07_BC for 1.7% 58 ; near-full-genome sequencing results show that many new CRFs have been generated in this region. [59][60][61][62] In India, subtype C is the predominant circulating subtype, [63][64][65][66] irrespective of the route of transmission, 67,68 and has been reported as one of the parental strains of CRF07_BC and CRF08_BC in China. 69 URFs of subtype C with B¢ are increasing, especially in the northeastern states.…”
Section: Hiv-1 Molecular Epidemiologymentioning
confidence: 99%